2006
DOI: 10.1080/14756360600748474
|View full text |Cite
|
Sign up to set email alerts
|

New progesterone derivatives as inhibitors of 5α-reductase enzyme and prostate cancer cell growth

Abstract: In this study we report the synthesis and pharmacological evaluation, in vivo as well as in vitro, of four new progesterone derivatives 4-7. The evaluation in vivo was carried out on gonadectomized male hamsters that were injected subcutaneously daily with 1 mg/Kg of testosterone (T) and/or 1 mg/Kg of finasteride, or with 2 mg/Kg of the novel compounds. It was observed that when testosterone (T) and finasteride or compound 4 were injected together, the weight of the prostate decreased significantly as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Some carbamates inhibit endothelial cell proliferation in vitro and tumor induced angiogenesis in vivo as well as tumor growth in mice [18]. In view of the fact that recently we have synthesized several progesterone derivatives with an ester moiety at C-17 which showed high activity as 5␣-reductase enzyme inhibitors and prostate cancer cell growth [19], in this paper, we describe the synthesis of two new steroids based on the progesterone skeleton having a carbamate moiety at C-17, compounds 8a and 8b (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Some carbamates inhibit endothelial cell proliferation in vitro and tumor induced angiogenesis in vivo as well as tumor growth in mice [18]. In view of the fact that recently we have synthesized several progesterone derivatives with an ester moiety at C-17 which showed high activity as 5␣-reductase enzyme inhibitors and prostate cancer cell growth [19], in this paper, we describe the synthesis of two new steroids based on the progesterone skeleton having a carbamate moiety at C-17, compounds 8a and 8b (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, these suggested endocrine interactions might be additionally influenced by an altered 5 ␣ -reductase metabolism, as has been indicated by previous experiments using inhibiting substances [26][27][28] . In a hamster model, in which the effects of progestin derivatives on prostate size were examined, it was suggested that these substances may act as 5 ␣ -reductase inhibitors and thereby avoid dihydrotestosterone-driven prostate growth increase, also interacting with the AR [29,30] . Unexpectedly, after the treatment change of groups with NETE, no significant prostate growth was measured in animals of group I.…”
Section: Discussionmentioning
confidence: 99%
“…Several new halogen substituted phenyl acetic acid ester derivatives of progesterone had been synthesized by our group which act as inhibitors of 5␣-reductase enzyme in human prostate [11]. However, these compounds did not bind to the androgen receptors (unpublished data).…”
Section: Introductionmentioning
confidence: 95%
“…The uteri from the rabbits were minced and homogenized in equal volume of TEMD buffer plus protease inhibitors (2 mM PMSF, 10 g/ml antipain, 5 mM leupeptin [14]; 40 mM Tris-HCl, 3 mM EDTA and 20 mM sodium molybdate, dithiotreitol 0.5 mM, 10% glycerol at pH 7.4) [11]. The homogenate was centrifuged at 140,000 × g for 1 h at 0 • C in a SW 60 Ti rotor (Beckman Instruments, Palo Alto, CA).…”
Section: Progesterone Receptormentioning
confidence: 99%